Bamboo as fiber reinforcement in concrete mix - Muhammad Maarof, Mustapha (2014)
Today they are many incorporated concrete with addition materials to improve the quality of the concrete. This study is focus on usage of the natural admixtures to be incorporated in the concrete mixtures specifically bamboo fiber. Bamboo has naturally characteristic which can grow fast, making it an easily replenish able resource. Bamboo is natural vegetation and normally grown in tropical countries. This fiber is made of cellulose and is being produced by processing methods such as steaming and boiling, and many more. By mixing a concrete using this material, it will give some advantages where more economical and reliable in term of quality and also supporting the load. This study was conducted to determine whether or not the bamboo fiber can be used as one of many materials to increase concrete durability (compression strength) quality and the flexural strength of the specimens and deflection of concrete mix with bamboo fiber. Concrete grade of 20 will be used during the preparation of the concrete mixture for the usage of the sample and sample incorporated with bamboo fiber with percentage of 1% and 3%. The results shows indicated a variety of bamboo fiber can be used, but with modest quantities and very minimal concrete tests performed. The concrete samples not incorporated with of bamboo fiber possessed the highest strength for both compression and flexural. The lowest strength which comprises compression and flexural goes to the concrete samples incorporated with 3% of bamboo fiber compared to the other two type of samples.